The Impact of the COVID-19 Quarantine on Sexual Life in Italy - Cito, Gianmartin; Micelli, Elisabetta; Cocci, Andrea; Polloni, Gaia; Russo, Giorgio Ivan; Coccia, Maria Elisabetta; Simoncini, Tommaso; Carini, Marco; Minervini, Andrea; Natali, Alessandro (Urology (Ridgewood, N.J.), 2021)
The aim of the study is to evaluate how individual and couple's sexuality had changed during the COVID-19 pandemic-related quarantine. A quantitative correlational research study was conducted, using a web-based survey. About 1576 participants were involved: 1018 women (64.6%) and 558 men (35.4%). A significant decline in the mean well-being scores during the quarantine, compared to before, was reported. A positive correlation between the well-being scores and the number of sexual intercourse (SI) before and during the quarantine was found. The mean number of SI decreased significantly during the quarantine. The main reasons were: poor privacy (43.2%) and lack of psychological stimuli (40.9%). About 1124 respondents (71.3%) did not report sexual desire (SD) reduction. A positive association between SD and SI during the quarantine was found. About 61.2% did not report autoerotism reduction. In those who reported decreased masturbation activity, the main causes were poor privacy (46.4%) and lack of desire (34.7%). We found that men presented lower SD during the quarantine, than women (P < 0.01). Potentially, the more time available might lead couples to reconnect at an intimate level and to improve their sexuality. However, the majority of quarantined participants experienced reduced number of SI per week, with poor household privacy and lack of psychological stimuli as cited causes, even as a majority did not report reduced autoeroticism.